2009
DOI: 10.1159/000242113
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Small Airway Function and Health Status, Dyspnea and Disease Control in Asthma

Abstract: Background: Small airways play important roles in the pathophysiology of asthma. However, relationships between small airway involvement and health status and dyspnea have not been investigated. Objectives: It was the aim of this study to assess the relationships between proximal and peripheral airway functions and health status, dyspnea and disease control in patients with asthma, using impulse oscillometry (IOS). Methods: We performed IOS, spirometry and assessment of health status (Asthma Quality of Life Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 95 publications
10
103
2
2
Order By: Relevance
“…Finally, it must be noted that, in our study, the increased values of DRrs5 Ϫ Rrs20 observed at day 15 were due to this lowering of Rrs20 and not to an increase of Rrs5, which was stable. This is relevant because an increment of DRs5-Rs20 has been proposed to be indicative of heightened peripheral airway resistance, [23][24][25] and, as our study suggests, this is not always true, because a relevant decrease of central airways resistance could also modify DRrs5 Ϫ Rrs20 in the same direction.…”
Section: Discussionmentioning
confidence: 72%
“…Finally, it must be noted that, in our study, the increased values of DRrs5 Ϫ Rrs20 observed at day 15 were due to this lowering of Rrs20 and not to an increase of Rrs5, which was stable. This is relevant because an increment of DRs5-Rs20 has been proposed to be indicative of heightened peripheral airway resistance, [23][24][25] and, as our study suggests, this is not always true, because a relevant decrease of central airways resistance could also modify DRrs5 Ϫ Rrs20 in the same direction.…”
Section: Discussionmentioning
confidence: 72%
“…Concerning the quality of life in asthmatic patients, a study using IOS found that R20, X5, and dose of ICS, but not FEV1, significantly accounted for the Asthma Quality of Life Questionnaire in multiple regression analyses (40).…”
Section: Asthmamentioning
confidence: 99%
“…59 The authors speculate that this might reflect ongoing improvement in small airway function in these patients. Two studies from Japan note that X RS relates more closely with quality of life measures than FEV 1 in both patients with asthma 60 and COPD. 61 One of the benefits of the FOT is that one can separately measure inspiratory from expiratory parameters.…”
Section: Measurement Of Airway Resistance By the Forced Oscillation Tmentioning
confidence: 99%